Human mobility in times of pandemic - García Saltos, Carmita Dolores (2022)
The coronavirus pandemic has placed greater emphasis on the binomials of human mobility; therefore, the article aims to analyze human mobility in times of pandemic, due to its devastating impact on the world. The analysis defines the number of migrants who have plummeted before this event, disrupting their dreams and future plans. It is concluded that migration passes through the contexts of political alliances between peoples and States, creating rights and obligations, but at the same time, conceptualizing the classic power over freedom, nationality and their basic rights in the face of clandestinely. Thus, determining the formation of possible constitutional reforms.